Differences in Blood Glucose Levels Before and After the Consumption of Sweet Tea in People in Marong Village - Aprilla, Annisa Suci; Diarti, Maruni Wiwin; Pauzi, Iswari; Jiwintarum, Yunan (Poltekkes Kemenkes Mataram, 2025)
Blood glucose is the body's main energy source and is greatly influenced by the consumption patterns of food and beverages, especially those containing sugar. Uncontrolled increases in blood glucose levels can lead to metabolic disorders such as Diabetes Mellitus. Consumption of sweetened tea containing added sugar can cause a rapid spike in blood glucose levels, especially when consumed regularly and in excessive amounts. The purpose of this study is to find out the difference in blood glucose levels before and after sweet tea consumption in the Marong Village community. This study uses a pre-experimental design with a one-group pretest-posttest approach. A total of 16 respondents were selected using the purposive sampling technique. Blood glucose levels were checked before and two hours after the consumption of sweet tea using the POCT (Point of Care Testing) tool. Data were analyzed using a statistical paired sample t-test. The results of the study showed obtained the average blood glucose level before the consumption of sweet tea was 88.3 mg/dL, and after consumption was 97.3 mg/dL, with an average difference of 8.3 mg/dL. The results of the paired sample t-test showed a significance value of 0.000 (p < 0.05), which means that there is a statistically significant difference. This study concludes that the consumption of sweet tea has a significant influence on increasing blood glucose levels.